2020
DOI: 10.1186/s12974-020-01979-y
|View full text |Cite
|
Sign up to set email alerts
|

Lectin complement pathway initiators after subarachnoid hemorrhage — an observational study

Abstract: Background This exploratory study investigated the time-course of lectin complement pathway (LCP) initiators in cerebrospinal fluid (CSF) and plasma in patients with subarachnoid hemorrhage (SAH), as well as their relationship to delayed cerebral ischemia (DCI) and functional outcome. Methods Concentrations of ficolin-1, ficolin-2, ficolin-3, and mannose-binding lectin (MBL) were analyzed in CSF and plasma from patients with SAH. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This hypothesis was supported by a previous observational study showing high prevalence of unmatched low-grade Hunt-Hess (74%∼89%) score accompanying with high grade Fisher score (79%∼88%) in elderly SAH population (11). Moreover, in comparison to their middle-aged counterparts, the similar low grade "atypical" group of SAH patients only accounted from 12.7% (in younger age group) to a maximum of 40% (not excluding the elder population) in previous cohorts (12)(13)(14)(15). Therefore, we speculate the typical clinical symptoms might only occur in elder patients upon a more massive blood diffused in subarachnoid space, in comparison to their younger counterparts (16).…”
Section: Discussionsupporting
confidence: 61%
“…This hypothesis was supported by a previous observational study showing high prevalence of unmatched low-grade Hunt-Hess (74%∼89%) score accompanying with high grade Fisher score (79%∼88%) in elderly SAH population (11). Moreover, in comparison to their middle-aged counterparts, the similar low grade "atypical" group of SAH patients only accounted from 12.7% (in younger age group) to a maximum of 40% (not excluding the elder population) in previous cohorts (12)(13)(14)(15). Therefore, we speculate the typical clinical symptoms might only occur in elder patients upon a more massive blood diffused in subarachnoid space, in comparison to their younger counterparts (16).…”
Section: Discussionsupporting
confidence: 61%
“…Higher plasma ficolin-1 levels were associated with worse initial clinical state, vasospasm, and DCI [ 226 ]. Studies demonstrated that patients with worse mRS scores at 3-month follow-up had higher CSF ficolin-1 and MBL levels (+1.87 and +1.69 ng/mL, respectively) [ 227 ]. The membrane attack complex (MAC, C5-C9 protein) was proposed to be particularly important in the inflammatory reaction.…”
Section: Biomarkers Of Inflammation: Acute-phase Protein Mmp-9 and Rn...mentioning
confidence: 99%
“…Given the uniform distribution of the negative charges and large size, UFH is able to stoichiometrically bind four oxyhemoglobin molecules neutralizing the toxic effects of free hemoglobin and related free radicals production in the CSF [168]. Furthermore, UFH has a number of anti-oxidant effects demonstrating a strong direct scavenging antioxidant effect neutralizing reactive oxygen species as occurred in several in vitro studies [56,57,[169][170][171]. In addition, UHF is able to increase the synthesis and release of extracellular SOD into circulating fluids [172,173].…”
Section: Heparin and Sahmentioning
confidence: 99%
“…Similarly, the initiators of lectin complement pathway (LCP), including ficolin-1, ficolin-2, ficolin-3, and mannose-binding lectin (MBL), have previously been investigated in SAH patients with inconclusive results that overall seem to suggest an association between plasma levels and severity of brain injury [53][54][55][56]. Matzen et al analysed the time-course of LCP initiator levels in CSF [57]. They found that LCP initiators increased during the first week after SAH and gradually declined over time.…”
Section: Complement In Csfmentioning
confidence: 99%